Elizabeth David: Is There a Nutmeg in the House? - D., J.M. (Petits Propos Culinaires, 2025)
Elizabeth David: Is There a Nutmeg in the House? Michael Joseph, 2000: ISBN 0-7181-4444-9: 322 pp., b/w illus., bibliog., index, h/b, £20.00.